Impactful Resistance: The Persistence of Recognition Politics in the Workplace. (January 2016) - Courpasson, David
Contrary to an ontology of defeatism that permeates scholarship on resistance, this paper suggests a perspective through which resistance can lead to hope and the unlikely victory of the powerless against the powerful. We offer an example where resisters develop specific activities that substantially modify a power relationship, thus showing the persistence of a recognition modality of impactful resistance on today's workplaces. The paper engages with recent accounts of post-recognition politics that largely deny the willingness of workers to struggle about issues related to work.